Islam et paysage au xvie siècle - Michèle Constans (Projets de Paysage)
Islamic culture is supposed to ignore landscape and to confine nature and territory esthetics in walled gardens and miniature paintings. The memories of first mughal emperor Babur express landscape and nature admiration, and tell about gardens and spatial planning projects that tresspass the quadripartite walled gardens ; it seems that islamics Timurids and Mughals had a landscape culture in visu and in situ.